Corema album spp: Edible wild crowberries with a high content in minerals and organic acids - Brito, Catarina (2020)
Edible wild plants are part of the ethnobotanical and gastronomic heritage of different geographical areas. Corema album (L.) D. Don is an endemic species of the dune systems of the Atlantic coast of the Iberian Peninsula. The aerial parts of Corema album are a source of nutrients and antioxidants. The Corema album white berry (Portuguese crowberry) is rich in calcium, iron, and zinc. The plant also shows high phenolic content and antioxidant capacity associated with the leaves, fruit, and flowers. The presence of organic acids, namely phenolic acids, such as hydroxycinnamic acids, and long chain polyunsaturated fatty acids (PUFAs) omega-3 and omega-6 has also been confirmed. Toxicity studies evaluated by cell viability tests with human intestinal epithelium model cells (Caco-2) have shown that, at low concentrations, plant extracts may present beneficial effects.